Evaluation Of Clinical Outcomes And Direct Medical Cost Of Anemia Management Among End Stage Renal Disease Patients In Khartoum State Hemodialysis Centers - Farag, Omalhassan Amir Abdelkarim (2017)
This research aimed to evaluate the prevalence of anemia, effectiveness of drug regimens, factors contributing to the control of hemoglobin levels, and factors contributing to cardiovascular events, hospitalizations, deaths, as well as, the annual direct medical costs of anemia treatment at government hemodialysis centers in Khartoum State, Sudan. This research was an observational prospective longitudinal study where all patients at the 12 dialysis centers were followed from August 2012 to July 2013. A total of 1015 patients were recruited in this study. Out of these, 194 (19.1%) patients were transferred to other centers, 165 (16.3%) died, 84 (8.3%) were lost during follow-up, and 38 (3.7%) underwent renal transplantation. A total of 534 (52.6%) patients completed the study and were included in the analysis. The majorities were males 307 (57.5%), the age ranged from 18-85 years, mean age was 48.7±16.1 years, and the median age was 50 years. The study found anemia in all the patients, hemoglobin level (<12 g/dL), whereas about 67% had a hemoglobin level <10 g/dL and only 20% had achieved the target Hb level (≥12 g/dL) in the last month. However, a significant improvement in mean Hb levels in seven drug regimens was found. Approximately 61% of patients received erythropoietin-stimulating agents (ESAs), and 87.1% received iron dextran. The most frequent anemia drugs regimen were 'ESA, intravenous (IV) iron, oral iron and vitamins (vitamin B12 and folic acid)' for 39.5% of the patients. Only 27% of the patients were tested for ferritin and transferrin saturation.